Advances in communication networks for pervasive and ubiquitous applications - Hussain, Sajid; Kausar, Firdous; Yang, Laurence T.; Khan, Farrukh A.; Park, Jong Hyuk (The Journal of supercomputing, 2013)
Advanced IT for Pervasive and Ubiquitous Computing (PUC) has presented a dramatic growth in merging the boundaries between physical space and cyberspace. In addition, PUC has rapidly emerged as an exciting new paradigm that tends to include different active research fields. This special issue called for high quality, up-to-date technology related ubiquitous and pervasive applications and state-of-the-art research issues. In particular, original and research articles are solicited in all aspects of including theoretical studies, practical applications, new communication technology, and software/system that address the challenges in various applications such as healthcare, industry automation, environment monitoring, military, and security. Finally, we have accepted only 14 manuscripts with high quality for this special issue. Furthermore, we expect that this special issue will be a trigger for further related research and technology improvements in this important subject.